Characteristics of gut microbiota of premature infants in the early postnatal period and their relationship with intraventricular hemorrhage - Yunlong Zhao; Shan Li; Rui Zhang; Xin Zhang; Qiuyue Shen; Xingyun Zhang; Tian Tian; Xinlin Hou (BMC Microbiology, 2024)
Abstract Background Studies have shown correlations between gut microbiota and neurocognitive function, but little was known about the early postnatal gut microbiota and intraventricular hemorrhage (IVH). We aimed to explore the characteristics of gut microbiota in premature infants and their relationship with IVH, further exploring potential therapeutic targets. Methods Premature infants delivered at Peking University First Hospital from February 2023 to August 2023 were recruited as a cohort. Feces samples were collected on postnatal days 1, 3, and 5. Premature infants were divided into normal, mild IVH, and severe IVH groups based on cranial ultrasound. 16S rRNA amplicon sequencing technology was used to determine the fecal microbiota, and the results were analyzed. Results Thirty-eight premature infants were enrolled. There was a significant difference in alpha and beta diversity among the three groups. The relative abundance of E. coli and A. muciniphila was different among the three groups. Further random forest analysis indicated that S. lutetiensis, L. mirabilis, and N. macacae can effectively distinguish premature infants with IVH. Finally, the phylogenetic investigation of communities by reconstruction of unobserved states2 (PICRUSt2) functional gene analysis predicted significant differences in energy metabolism, carbohydrate metabolism, metabolism of cofactors and vitamins, and membrane transport between normal and severe IVH groups. Conclusions The gut microbiota in the early postnatal period of premature infants is closely associated with the IVH status. As age increases, the differences in gut microbiota of premature infants with different degrees of IVH continue to increase, and the trend of changes with severity of IVH becomes more and more obvious. E. coli, A. muciniphila, S. lutetiensis, L. mirabilis, N. macacae, G. haemolysans, and S. oralis can effectively distinguish between IVH infants and normal premature infants. The results indicate that gut microbiota is expected to provide effective therapeutic targets for the diagnosis and treatment of IVH.